Tool for automated simulation of solar arrays using general-purpose simulators - Kasparis, Takis; Pongratananukul, Nattorn (My University, 2004)
The paper describes a tool developed to automate the study of solar array configurations using a general-purpose simulator such as Spice. The main advantage of the proposed method is that studies can be done for any solar array configuration formed from elementary models of solar cell units. Hierarchical structure of solar cell elements with semiconductor detail allows simulations of electrical properties as well as evaluation of environmental conditions impact Application examples such as the effect of unequal illumination on various array interconnections and the mismatch of solar cells will be presented to demonstrate the usefulness of the tool. The automated process will ease investigation of large system and worst-case study for given environmental scenarios.
Keywords: Automation; Computer simulation; Computer software; Energy conversion